Exploring the adoption of Enterprise Metaverse in Business-to-Business (B2B) organisations - Biswas, Baidyanath (Elsevier, 2025)
The present study investigates the propensity of organisations to adopt the Enterprise Metaverse. This research reveals that organisational readiness, facilitating conditions, performance expectancy, and normative and mimetic pressures are significantly associated with adopting the Enterprise Metaverse. Additionally, trust significantly mediates the relationship between organisational competency, organisational complexity, performance expectancy, effort expectancy, mimetic pressures and adopting the Enterprise Metaverse. Also, the findings reveal that trust and management support play a crucial mediating and moderating role in the present context. Finally, the Artificial Neural Network (ANN) results indicate normative pressures as the most important predictor of adopting the Enterprise Metaverse. The study's outcomes are set to enhance the Metaverse literature significantly. Moreover, it aims to deepen the comprehension of B2B technology adoption, drawing from the theoretical foundations of the Unified Theory of Acceptance and Use of Technology (UTAUT), the Technology–organisation–environment (TOE) framework, and institutional theory. This research offers organisations valuable insights into the determinants linked to integrating the Enterprise Metaverse.
PUBLISHED
Keywords: Metaverse, UTAUT, Enterprise Metavers, TOE framework, Institutional Theory, Trust; Digital Engagement; Digital Platform